Targeting Inflammation With Nanosized Drug Delivery Platforms in Cardiovascular Diseases: Immune Cell Modulation in Atherosclerosis - Cervadoro, Antonio; Palomba, Roberto; Vergaro, Giuseppe; Cecchi, Roberta; Menichetti, Luca; Decuzzi, Paolo; Emdin, Michele; Luin, Stefano (Frontiers in Bioengineering and Biotechnology, 2018)
Atherosclerosis (AS) is a disorder of large and medium-sized arteries; it consists in the formation of lipid-rich plaques in the intima and inner media, whose pathophysiology is mostly driven by inflammation. Currently available intervention and therapies for treating atherosclerosis are not always completely effective; side effects associated with treatments, mainly derived by immunodepression for anti-inflammatory molecules, limit the systemic administration of these and other drugs. Given the high degree of freedom in the design of nanoconstructs, in the last decades researchers have put high effort in the development of nanoparticles (NPs) formulations specifically designed for either drug delivery, visualization of atherosclerotic plaques, or possibly the combination of both these and other functionalities. Here we will present the state of the art of these subjects, the knowledge of which is necessary to rationally address the use of NPs for prevention, diagnosis, and/or treatment of AS. We will analyse the work that has been done on: a) understanding the role of the immune system and inflammation in cardiovascular diseases, b) the pathological and biochemical principles in atherosclerotic plaque formation, c) the latest advances in the use of NPs for the recognition and treatment of cardiovascular diseases, d) the cellular and animal models useful to study the interactions of NPs with the immune system cells.